in Silico Microsatellite Development in Arum Lily (Zantedeschia aethiopica) - V Radhika (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2011)
Microsatellites are an important class of molecular markers having wide application in genetic research. Development of microsatellites using conventional methods is laborious and expensive. Alternatively, in silicoapproach can be followed to detect simple sequence repeats (SSRs) from expressed sequence tags (ESTs) available in public biological databases. The in silico developed EST-SSRs have been found to be transferrable across species and genera. A study was undertaken to mine simple sequence repeats (SSRs) from the expressed sequence tags (ESTs) of arum lily, Zantedeschia aethiopica, belongs to the family Araceae. A total of 4283 ESTs of Zantedeschia aethiopica, downloaded from dbEST of NCBI, were pre-processed and subjected to clustering and assembly. In all, 1968 clusters (800 contigs and 1168 singletons) were obtained, resulting in 54 % reduction in ESTs. In addition, 1936 SSRs were obtained, which included 617 mono, 101 di-, 201 tri-, 80 tetra-, 23 penta- and 898 hexa-nucleotide repeats. The plant has an abundance of 0.70 SSRs/ kb. We designed 1091 primers for these SSRs. A few in silico designed SSR primers were tested for polymorphism in Anthurium, belonging to the Araceae family, resulting in 40% amplification success.